Does normobaric hypoxic resistance training confer benefit over normoxic training in athletes? A narrative review - Deldicque, L. (Journal of Science in Sport and Exercise, 2022)
Purpose The aim of the present review was to focus on normobaric hypoxic resistance training and to discuss to what extent this method can be efficient for athletes to potentiate classical adaptations to resistance training and thereby performance.